Constitutive models for peat - A review - O'Kelly, Brendan (International Center for Numerical Methods in Engineering (CIMNE), Barcelona, Spain, 2013)
This paper presents a review of the main constitutive models for peat and other highly organic soils having extremely high water content. At present, predictions of the geomechanical behaviour of such soils for design practice are mostly based on constitutive theories developed for fine-grained mineral soils. Concepts of primary consolidation and secondary compression as applied to peat are explained using the two-level structure assumption of micropores and macropores [1]. As background, the historical development of consolidation hypotheses A&B [24] regarding the concepts of primary consolidation and secondary compression is reviewed for both mineral and organic soils. Based on microscopic examinations and in-situ testing, it is generally accepted that hypothesis B is more suitable for peat. The micro-mechanical rheological model proposed by Berry and Poskitt [2] and the isotache-compression model developed by den Haan [6] were reported to have good agreement with experimental laboratory results for fibrous and amorphous peats. Attention is given to the structural anisotropy of peat material, inherent by its fibrous nature, in these constitutive frameworks.
Computational Plasticity XII: Fundamentals and Applications - Proceedings of the 12th International Conference on Computational Plasticity - Fundamentals and Applications (COMPLAS 2013)
PUBLISHED
Barcelona, Spain
Keywords: Constitutive model; Consolidation hypothesis; Peat; Organic soils; Structural anisotropy